(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2009)
The study was carried out in order to assess the impact of the various pollutants of textile dyeing effluents on the surface water quality of the industrial area inside Dhaka-Narayanganj-Demra (D.N.D) embankment, Narayanganj. Physicochemical parameters such as TSS, TDS, DO, pH, EC, Turbidity, BOD, COD, anionic parameters such as F-, Cl-, NO2 -, NO3 -, SO4 - and PO4 3- and heavy metals such as Pb, Zn, Cd and Cu of the samples were investigated by using various techniques. The results showed that, textile dyeing industries inside D.N.D embankment area discharges effluents composed of various physicochemical and anionic pollutants at considerably higher level compared to pollution limit. Further, the surface water of the D.N.D channel, ponds and lakes around the studied textile dyeing industries also contain various physicochemical and anionic pollutants at intolerable limit. A significant correlation was also observed among some important water parameters of the effluents and surface water. The above findings point out that the surface water around the studied textile dyeing industries is highly polluted by the industrial activities of the D.N.D. embankment area and not good for human consumption. Key words: Industrial effluents, D.N.D embankment, Surface water quality, Environmental impact. doi: 10.3329/bjsir.v44i1.2715 Bangladesh J. Sci. Ind. Res. 44(1), 65-80, 2009